The efficacy of sterilizing agents, copper oxychloride, vegetable oil and agrowipe (botanic neem extract) against crown gall disease of roses in Kericho, Kenya - Oniang’o Mary, Opisa; Oliver Stafford, Achwanya; Daniel Otieno, Otaye; Japheth Mburugu, Muthamia (African Science Publications, 2020)
The experiments were conducted at James Finlay Kenya, flowers division Tarakwet farm in Kericho county from January 2016 to December 2016 to study the efficacy of copper oxychloride 1.0 g/L, hydrogen peroxide 1.0 ml/L, dettol 0.5 mL/L and 1.0 mL/L, agrowipe undiluted and fresh fri undiluted as control agents of crown gall disease in roses. Crown gall causes losses of between 75-95% on susceptible rose varieties hence the need to develop effective control strategies. Results showed plots treated with agrowipe and fresh fri had higher yield of roses, which were of better quality, longer, heavier and also inhibited growth of crown gall tumors and fresh crown gall growths compared to copper oxychloride at 1.0 g/L and untreated control. Dettol at 0.5 mL/L, 1.0 mL/L and hydrogen peroxide 1.0 mL/L had moderate yield of roses and crown gall control. Similar results were observed in the pot trials. Agrowipe and fresh fri effectively controlled crown gall diseases hence were recommended for use in controlling crown gall disease in roses in Kenya.
Keywords: Agrowipe, Crown gall, Control agents, Tumor, Roses